Salivary and lacrimal dysfunction after radioactive iodine for differentiated thyroid cancer: American Head and Neck Society Endocrine Surgery Section and Salivary Gland Section joint multidisciplinary clinical consensus statement of otolaryngology, ophthalmology, nuclear medicine and endocrinology. Issue 11 (19th August 2020) - Singer, Michael C.; Marchal, Francis; Angelos, Peter; Bernet, Vic; Boucai, Laura; Buchholzer, Samanta; Burkey, Brian; Eisele, David; Erkul, Evren; Faure, Frederic; Freitag, Suzanne K.; Gillespie, Marion Boyd; et al.
Abstract: Background: Postoperative radioactive iodine (RAI) administration is widely utilized in patients with differentiated thyroid cancer. While beneficial in select patients, it is critical to recognize the potential negative sequelae of this treatment. The prevention, diagnosis, and management of the salivary and lacrimal complications of RAI exposure are addressed in this consensus statement. Methods: A multidisciplinary panel of experts was convened under the auspices of the American Head and Neck Society Endocrine Surgery and Salivary Gland Sections. Following a comprehensive literature review to assess the current best evidence, this group developed six relevant consensus recommendations. Results: Consensus recommendations on RAI were made in the areas of patient assessment, optimal utilization, complication prevention, and complication management. Conclusion: Salivary and lacrimal complications secondary to RAI exposure are common and need to be weighed when considering its use. The recommendations included in this statement provide direction for approaches to minimize and manage these complications.